Analyzing Factors Affecting the Behavioral Intention to Use e-Wallet with the UTAUT Model with Experience as Moderating Variable - Tusyanah, Tusyanah; Wahyudin, Agus; Khafid, Muhammad (Universitas Negeri Semarang, 2020)
The objective of the study is to analyze the factors on the behavioral intention to use e-Wallet based on the UTAUT model. The variables are performance expectancy, effort expectancy, social influence, facilitating conditions, and experience as a moderating variable. It is quantitative research. Data were collected by questionnaire and analyzed using SEM-PLS. The population in this study was students of the Faculty of Economics at Universitas Negeri Semarang who have adopted cashless transactions in their payment activities. The population in this study was 4,156 students, with a sample of 365 students. The results of this study show that performance expectancy has a positive and significant effect on the behavioral intention for 18.4 %, Effort expectancy has a positive and significant effect on the behavioral intention for 20.1%, Social influence has a positive and significant effect on behavioral intentions for 22.8 %, Facilitating condition has a positive effect and significant impact on the behavioral intention for 24.7%, Effort expectancy has a positive and significant effect on behavioral intention through experience (moderating 1) for 24.6 %, Social influence has a negative effect and insignificant effect on behavioral intentions through experience (moderating 1) for -4.8 %, and Facilitating condition has a negative and insignificant effect on behavioral intentions through experience (moderating 1) for - 5.3 %.